THE EFFECT OF TRAINING AND CAREER DEVELOPMENT ON IMPROVING EMPLOYEE PERFORMANCE AT THE OFFICE OF THE PORT AUTHORITY AND PORT AUTHORITY CLASS III KUALA TANJUNG - Ika Ramadani; Muhammad Haikal Khadafi; Aisyah Sirgear; Willy Cahyadi (CV. Radja Publika, 2025)
This study aims to determine the effect of training and career development on improving employee performance at the Kuala Tanjung Class III Harbormaster and Port Authority Office. The analytical methods used in this study include instrument testing, namely validity and reliability. Classical tests include normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, coefficient of determination (R2) analysis, and hypothesis testing using the T-test and F-test. The results indicate that training has no effect on improving employee performance, career development does, and training and career development simultaneously influence employee performance.